2014
DOI: 10.1002/ece3.1028
|View full text |Cite
|
Sign up to set email alerts
|

Fitness dynamics within a poplar hybrid zone: II. Impact of exotic sex on native poplars in an urban jungle

Abstract: Trees bearing novel or exotic gene components are poised to contribute to the bioeconomy for a variety of purposes such as bioenergy production, phytoremediation, and carbon sequestration within the forestry sector, but sustainable release of trees with novel traits in large-scale plantations requires the quantification of risks posed to native tree populations. Over the last century, exotic hybrid poplars produced through artificial crosses were planted throughout eastern Canada as ornamentals or windbreaks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…deltoides . They also found that the majority of gene flow (more than 98%) was intraspecific [23, 24]. DiFazio et al reported that the mean pollination distance for P .…”
Section: Discussionmentioning
confidence: 99%
“…deltoides . They also found that the majority of gene flow (more than 98%) was intraspecific [23, 24]. DiFazio et al reported that the mean pollination distance for P .…”
Section: Discussionmentioning
confidence: 99%
“…The genus Populus is presented by dioecious species and, due to extensive genetic studies ( Tuskan et al, 2006 ; Jansson and Douglas, 2007 ; Jansson et al, 2010 ), is a promising object for research of differences between sexes. Poplars are wind-pollinated trees, and different species are easily crossed, resulting in the emergence of natural interspecific hybrids and a high level of genetic diversity ( Rae et al, 2007 ; Roe et al, 2014 ; Jiang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Poplars are dioecious wind-pollinated plants that leads to high intraspecies diversity (Rae et al, 2007). It is known that various species of poplar are easily crossed forming natural interspecific hybrids (Roe et al, 2014;Jiang et al, 2016) that poses difficulties in identifying their taxonomic status. Genome of P. trichocarpa was sequenced in 2006 being the first genome of a tree (Tuskan et al, 2006).…”
Section: Plant Geneticsmentioning
confidence: 99%